Guideline on multimodal rehabilitation for patients with post-intensive care syndrome - Caroline Renner; Marie-Madlen Jeitziner; Monika Albert; Sabine Brinkmann; Karin Diserens; Imanuel Dzialowski; Maria-Dorothea Heidler; Martina Lück; Ricki Nusser-Müller-Busch; Peter S. Sandor; Andreas Schäfer; Bettina Scheffler; et al. (Critical Care, 2023)
Abstract Background Intensive Care Unit (ICU) survivors often experience several impairments in their physical, cognitive, and psychological health status, which are labeled as post-intensive care syndrome (PICS). The aim of this work is to develop a multidisciplinary and -professional guideline for the rehabilitative therapy of PICS. Methods A multidisciplinary/-professional task force of 15 healthcare professionals applied a structured, evidence-based approach to address 10 scientific questions. For each PICO-question (Population, Intervention, Comparison, and Outcome), best available evidence was identified. Recommendations were rated as “strong recommendation”, “recommendation” or “therapy option”, based on Grading of Recommendations, Assessment, Development and Evaluation principles. In addition, evidence gaps were identified. Results The evidence resulted in 12 recommendations, 4 therapy options, and one statement for the prevention or treatment of PICS. Recommendations: early mobilization, motor training, and nutrition/dysphagia management should be performed. Delirium prophylaxis focuses on behavioral interventions. ICU diaries can prevent/treat psychological health issues like anxiety and post-traumatic stress disorders. Early rehabilitation approaches as well as long-term access to specialized rehabilitation centers are recommended. Therapy options include additional physical rehabilitation interventions. Statement: A prerequisite for the treatment of PICS are the regular and repeated assessments of the physical, cognitive and psychological health in patients at risk for or having PICS. Conclusions PICS is a variable and complex syndrome that requires an individual multidisciplinary, and multiprofessional approach. Rehabilitation of PICS should include an assessment and therapy of motor-, cognitive-, and psychological health impairments.